Urban land regularization as a means of fixing the rights to property and worthy dwelling: a way to solve the social problem of informative cores in large urban centers / A regularização fundiária urbana como meio de garantir os direitos à propriedade e à habitação digna: uma forma de resolver o problema social dos núcleos informais em grandes centros urbanos - Ricci, Erwin Rodrigues; Filho, Adalberto Simão (Revista de Direito da Cidade, 2020)
Abstract In this scientific article will be analyzed the provision brought by Law 13.465 / 2017 and Decree 9.310 / 2018, more precisely regarding Urban Land Regularization. The focus of this paper will be the analysis of fundamental rights to housing and property. A correlation will be made on how urban land regularization can serve as an effective tool in the realization of these fundamental rights. For this, the analysis of its concepts and procedures, its characteristics and functions will be realized. It also analyzes the consequences and legal effects of the acquisition of property through Urban Land Tenure Regulation, based on the principles and effects deriving from Public Registries, as well as the fundamental role of this extrajudicial procedure for the adjudication of demands. Keywords: Urban Land Regularization; Fundamental rights; Property; Public Records; Resumo Neste artigo científico será analisada a disposição trazida pela Lei 13.465 / 2017 e pelo Decreto 9.310 / 2018, mais precisamente em relação à Regularização Fundiária Urbana. O foco deste artigo será a análise dos direitos fundamentais à moradia e à propriedade. Será feita uma correlação sobre como a regularização fundiária urbana pode servir como uma ferramenta eficaz na realização destes direitos fundamentais. Para isso, a análise de seus conceitos e procedimentos, suas características e funções será realizada. Também serão analisadas as consequências e efeitos legais da aquisição de imóveis através da Regularização Fundiária Urbana, com base nos princípios e efeitos derivados dos Registros Públicos, bem como o papel fundamental deste procedimento extrajudicial para a adjudicação de demandas. Palavras-chave: Regularização fundiária urbana; Direitos fundamentais; Propriedade; Registros Públicos;